2019
DOI: 10.1038/s41386-019-0384-x
|View full text |Cite
|
Sign up to set email alerts
|

Hypophagia induced by hindbrain serotonin is mediated through central GLP-1 signaling and involves 5-HT2C and 5-HT3 receptor activation

Abstract: The overlap in neurobiological circuitry mediating the physiological and behavioral response to satiation and noxious/stressful stimuli are not well understood. The interaction between serotonin (5-HT) and glucagon-like peptide-1 (GLP-1) could play a role as upstream effectors involved in mediating associations between anorectic and noxious/stressful stimuli. We hypothesize that 5-HT acts as an endogenous modulator of the central GLP-1 system to mediate satiation and malaise in rats. Here, we investigate wheth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 75 publications
(104 reference statements)
7
17
0
Order By: Relevance
“…We then tested the ability of Ond to attenuate pica, anorexia, and the consequent body weight loss induced by GDF15. Systemic Ond pre-treatment by itself did not affect food intake nor body weight and did not stimulate kaolin intake compared to their relative controls ( Figures 4A-4C), corroborating previous reports (Hayes and Covasa, 2006;Leon et al, 2019). Post hoc analysis revealed that systemic Ond pre-treatment was effective in attenuating GDF15-induced anorexia, leading to greater food intake compared to GDF15treated animals at 24 h and 48 h, respectively.…”
Section: Systemic But Not Hindbrain Ondansetron Partially Attenuatesupporting
confidence: 89%
See 2 more Smart Citations
“…We then tested the ability of Ond to attenuate pica, anorexia, and the consequent body weight loss induced by GDF15. Systemic Ond pre-treatment by itself did not affect food intake nor body weight and did not stimulate kaolin intake compared to their relative controls ( Figures 4A-4C), corroborating previous reports (Hayes and Covasa, 2006;Leon et al, 2019). Post hoc analysis revealed that systemic Ond pre-treatment was effective in attenuating GDF15-induced anorexia, leading to greater food intake compared to GDF15treated animals at 24 h and 48 h, respectively.…”
Section: Systemic But Not Hindbrain Ondansetron Partially Attenuatesupporting
confidence: 89%
“…103639-04-9)was either dissolved in artificial cerebrospinal fluid (aCSF; Harvard Apparatus, Cat. 59-7316) for icv delivery (25 µg) or dissolved in 0.9% saline and injected at 1 mg/kg ip as previously described (Hayes and Covasa, 2006;Leon et al, 2019). LiCl (0.15 M in 0.9% saline, 20 mL/kg, Sigma Aldrich, Cat.…”
Section: Methods Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a growing number of studies, Exenatide, a long‐acting glucagon‐like peptide 1 (GLP‐1) analog, has been reported to stimulate neurogenesis, suppress inflammation, and have healing effects on behavior by showing antioxidant properties in the central nervous system (CNS) (Perry et al, 2003; Solmaz et al, 2015). In addition, GLP has also been shown to have modulatory effects on serotonin and GABA in CNS (Leon et al, 2019; Rebosio, Balbi, Passalacqua, Ricciarelli, & Fedele, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the family of receptors 5-HT2, and the receptors 5-HT1A and 5-HT3 have been implicated in satiety signalization specifically in the NTS, through activation of GLP-1 producing neurons (20,30,31). Despite we know this, much remains to be elucidated, especially with regard to its responses to environmental stimuli.…”
Section: Discussionmentioning
confidence: 99%